2022
DOI: 10.3724/sp.j.1042.2022.00486
|View full text |Cite
|
Sign up to set email alerts
|

Social exclusion influenced intertemporal decision-making and its mechanism

Abstract: Social exclusion exists widely, has a negative impact on human cognition, affection and behavior. It impairs individual's cognitive function and results in difficulties in making rational judgements and decisions. Studies showed that people who experienced social exclusion tended towards risk seeking in risky decision making. Intertemporal decision-making is a particular type of decision-making and it has high similarity with risk decision-making in theoretical development and neural basis. However, whether an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…As economic scarcity impairs cognitive functioning, time scarcity also impairs individual cognitive and behavioral performance. Studies by Spears (2011) and Zhang (2019) also found that manipulating scarce situations in a laboratory can lead to worse performance in inhibitory control tasks. Zhao (2014) found that in the 6 weeks before the final exam of college students, their performance on Raven’s reasoning task (a task to measure fluid intelligence) declined.…”
Section: Discussionmentioning
confidence: 96%
“…As economic scarcity impairs cognitive functioning, time scarcity also impairs individual cognitive and behavioral performance. Studies by Spears (2011) and Zhang (2019) also found that manipulating scarce situations in a laboratory can lead to worse performance in inhibitory control tasks. Zhao (2014) found that in the 6 weeks before the final exam of college students, their performance on Raven’s reasoning task (a task to measure fluid intelligence) declined.…”
Section: Discussionmentioning
confidence: 96%
“…This result is supported by empirical scientific research (Shah et al, 2012), indicating that individuals become more fatigued and less attentive when facing laboratory-designed scarcity in chances, time, and economy and borrow large sums of money regardless of the interest rate. Studies by Spears (2011) and Zhang (2019) found that compared with non scarcity circumstances, people exhibit worse performance in tasks requiring self-control under manipulated scarcity circumstances. In addition, people generally focus on their urgent needs and neglect remote aims (Soyoun et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on how it is measured, social exclusion can be categorized into long-term social exclusion (trait level) and short-term social exclusion (state level). Long-term social exclusion can be examined through questionnaire measurements and short-term social exclusion can be induced through experiments (Zhang et al, 2022). The general aggression model (GAM; Anderson & Bushman, 2002) states that situational factors influence aggression through cognition, emotion, and arousal.…”
Section: Social Exclusion and Aggressionmentioning
confidence: 99%